Study of the Use of Seagrass Bait on Bebihe Catches in the waters of the Sea Beg, South Central Tabukan District, Sangihe Islands Regency - Larungkondo, Jerialdy; Labaro, Ivor Lembondorong; Pangalila, Fransisco P.T.; Budiman, Johnny; Manoppo, Lefrand; Silooy, Fanny (Sam Ratulangi University, 2022)
AbstractBubu fisheries have developed well in all Indonesian waters, especially in coastal areas that have coral reef and seagrass habitats. Generally, the commodities targeted for fishing are types of reef fish and seagrass beds that have a high selling value, such as snapper, grouper, baronang, yellowtail, lobster, octopus, and others. Bubu fishing gear or traps called bebihe local people are one of the fishing gear used to catch demersal fish or reef fish. The success of the bubu fishing operation is greatly influenced by the construction of the bebihe fishing gear itself and the treatment of the bait used. The use of seagrass bait, allegedly can increase the catching ability of the bebihe. However, scientific information on the use of seagrass as a bait for bebihe for fishing is not yet available. Therefore, the purpose of this study is to determine the effectiveness of seagrass baits with the comparison of kitefish in the operation of bebihe; and identify the types of fish caught.This research was carried out in the waters of Beeng Laut island, South Central Tabukan District, Sangihe Islands Regency; is based on experimental methods. Six bebihe units were operated during nine trips to collect data; where three units use seagrass bait of the type Thalassia hemprichii, and the other three units use kite fish bait; and then the catch data is analyzed by a t-test.The catch of bebihe during the study amounted to 363 heads, as many as 345 were caught with seagrass baits, and 18 were caught with kite baits. Analysis of the t-test showed that at t count = 5.480 > t table 0.05;8 = 2.306; where this explains that the use of seagrass bait on bebihe, gives a noticeablely different catch compared to kitefish bait.